Genome-wide identification of the phosphofructokinase gene family in maize (Zea mays L.) and their expression levels under abiotic stress and phytohormones - Weichao Fu; Delong Fan; Shenkui Liu; Yuanyuan Bu (BMC Plant Biology)
Abstract Background Phosphofructokinase (PFK) is the primary rate-limiting enzyme and regulatory site of the glycolysis process, which is crucial for plant growth and the regulation of stress response. The PFK genes in Arabidopsis (Arabidopsis thaliana), wheat (Triticum aestivum), rice (Oryza sativa), cotton (Gossypium spp.) and potato (Solanum tuberosum) have been comprehensively analyzed. However, the PFK genes in maize (Zea mays L.) have not been systematically studied. Results In this study, we performed a comprehensive bioinformatic analysis of the maize genome and identified 18 ZmPFK genes. Phylogenetic analysis indicated that these genes are divided into 5 subfamilies. The evolutionary patterns and divergence levels indicate that ZmPFK genes were present before the divergence of dicotyledons and have been highly conserved, undergoing purifying selection through out evolution. Expression analysis showed that most ZmPFK genes exhibited variable expression levels across different tissues and developmental stages. Based on transcriptome data and promoter element analysis, we specifically focused on eight ZmPFK genes whose promoters contained numerous plant hormones and stress response elements. These genes were up-regulated under different abiotic stresses as confirmed by RT-qPCR analysis, highlighting their important roles in plant growth and stress response. Conclusions In this study, the structure, location and evolutionary relationship of maize PFK gene family members were analyzed for the first time. We identified the ZmPFK genes involved in stress and plant hormone response by combining promoter element analysis, transcriptome data, and RT-qPCR analysis. This study provides valuable insights into the involvement of maize glycolysis in stress response.